Economic preferences and attitudes of the unemployed: Are natives and second generation migrants alike? - Amelie F. Constant; Annabelle Krause; Ulf Rinne; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In this paper we study the economic effects of risk attitudes, time preferences, trust and reciprocity while we compare natives and second generation migrants. We analyze an inflow sample into unemployment in Germany, and find differences between the two groups mainly in terms of risk attitudes and positive reciprocity. Second generation migrants have a significantly higher willingness to take risks and they are less likely to have a low amount of positive reciprocity when compared to natives. We also find that these differences matter in terms of economic outcomes, and more specifically in terms of the employment probability about two months after unemployment entry. We observe a significantly lower employment probability for individuals with a high willingness to take risks. Some evidence suggests that this result is channeled through reservation wages and search intensity.
Keywords: F22; J15; J61; J64; 330; Unemployment; Migration; Personality Traits; Risk Attitudes; Time Preferences; Trust; Reciprocity